Students’ Satisfaction with Service Quality of Community Campuses in Gandaki Province, Nepal - Acharya, Bishnu (Myagdi Guru, 2024)
This study aims to assess student satisfaction with campus facilities at community campuses in Gandaki Province, Nepal, using the SERVQUAL model. The main objectives are to evaluate students’ satisfaction with the provided facilities and to examine the relationship between the dimensions of these facilities and overall student satisfaction. A quantitative research approach along with descriptive and causal research design were employed. Data was collected from 143 bachelor’s and master’s level students in management, education, and humanities faculties from three campuses. The data collection was done through a well-constructed questionnaire distributed via Google Forms. Statistical tools, including multiple regression and Pearson correlation analyses, were used to present and analyze the data. The results indicate a generally positive perception of institutional facilities, with the assurance dimension scoring highest (mean = 3.771) and responsiveness scoring lowest (mean = 3.372). Empathy emerged as the most significant factor influencing student satisfaction (β = 0.282, p < 0.05), followed by reliability (β = 0.277, p < 0.05) and tangibility (β = 0.191, p < 0.05). The findings underscore the importance of personalized attention, consistent service delivery, and well-maintained facilities in enhancing student satisfaction. This study provides valuable insights for campus management to improve facilities, thereby aiding in student retention and attraction.